A stabilized finite point method for analysis of fluid mechanics problems - Oñate, E.; Idelsohn, S.; Zienkiewicz, O.C.; Taylor, R.L.; Sacco, C. (Computer methods in applied mechanics and engineering, 1996)
In this paper a meshless procedure termed ‘the finite point method’ for solving convection-diffusion and fluid flow type problems is presented. The method is based on the use of a weighted least-square interpolation procedure together with point collocation for evaluating the approximation integrals. Special emphasis is given to the stabilization of the convective terms and the Neumann boundary condition which has been found to be essential to obtain accurate results. Some examples of application to diffusive and convective transport and compressible flow problems using quadratic FP interpolations are presented.